Time perspective and decision-making: a study on decisional patterns in argentinian adults - Fernández Da Lama, Rocío Giselle (2023)
Fil: Fernández Da Lama, Rocío Giselle. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina